Catalytic synthesis of mixed alcohols mediated with nano-MoS2 microemulsions. (15th January 2016) - Hasty, Julia K.; Ponnurangam, Sathish; Turn, Scott; Somasundaran, P.; Kim, Taejin; Mahajan, Devinder
Abstract: Supported micron-sized molybdenum disulfide (MoS2 ) has been extensively studied for catalytic synthesis of Higher Alcohols Synthesis (HAS) from synthesis gas (syngas). However, the process is associated with low space–time–yield (STY) and poor selectivity under high temperature (300–325 °C) and high pressure (10–20 MPa) operation, making it unattractive for commercial application. Nano-sized MoS2 catalyst particles improve selectivity to alcohols but the yields are low possibly due to catalyst aggregation and mass transfer limitations. This study describes the use of oil-in-polyethylene glycol (PEG) microemulsion-based encapsulation of hydrophobic catalyst nanoparticles (MoS2 ) to prevent aggregation, increase surface area and increase mass transfer across the two phases. In this study, nano-sized MoS2 was first synthesized by sonolysis of hexacarbonyl molybdenum and yellow sulfur in hexadecane in <90% yield, mixed with non-ionic surfactant (Tergitol NP-8) and the mixture was slurried in two solvents: PEG-400 or Ethylflo-164 (a C30 oil). The slurred nano MoS2 was evaluated for syngas (H2 /CO = 2:1) conversion into higher alcohols in a 300 mL stirred batch reactor. Our results showed increased STY, reaching 1.2 kg alcohols/kg catalyst/h. The corresponding product selectivity reached 62 wt% methanol and 52 wt% to ethanol, respectively in two separate runs when microemulsion-based catalysts were employed. These results open up the possibility of a novel and efficient route to higher alcohols.